Dynamics of CO2 and CH4 fluxes in Red Sea mangrove soils - J. Breavington; A. Steckbauer; C. Fu; M. Ennasri; C. M. Duarte (Biogeosciences)
Red Sea mangroves have a lower carbon burial rate than the global average, whereby small greenhouse gas fluxes may offset a large proportion of carbon burial. Monthly soil core sampling was conducted across 2 years at two sites within a central eastern Red Sea mangrove stand to examine carbon dioxide (CO2) and methane (CH4) fluxes under dry and inundated conditions. Fluxes were highly variable, characterized by a prevalence of low emissions punctuated by bursts of high emissions. At the landward site, average ± SE (median) flux from the soil–air interface was 3111 ± 929 (811) µmol CO2 m−2 d−1 and​​​​​​​ 1.68 ± 0.63 (0.26) µmol CH4 m−2 d−1 under light conditions and 8657 ± 2269 (1615) µmol CO2 m−2 d−1 and 0.84 ± 0.79 (0.59) µmol CH4 m−2 d−1 under dark conditions. Average ± SE (median) sea–air fluxes were −55 ± 165 (−79) µmol CO2 m−2 d−1 and 0.12 ± 0.23 (0.08) µmol CH4 m−2 d−1 under light conditions and 27 ± 48 (53) µmol CO2 m−2 d−1 and 0.16 ± 0.13 (0.09) µmol CH4 m−2 d−1 in dark conditions. The seaward site recorded a higher CH4 flux, averaging 18.7 ± 8.18 (1.7) and 17.1 ± 4.55 (7.7) µmol CH4 m−2 d−1 in light and dark conditions. Mean fluxes offset 94.5 % of carbon burial, with a median of 4.9 % skewed by extreme variability. However, reported CO2 removal by total alkalinity emission from carbonate dissolution greatly exceeded both processes and drives the role of these ecosystems as intense CO2 sinks.